Intercultural contents, a public policy to democratize communication in Ecuador. Study in the newspapers La Hora Esmeraldas and El Norte de Imbabura.: Intercultural contents, a public policy to democratize communication in Ecuador. Study in the newspapers La Hora Esmeraldas and El Norte de Imbabura - Solis, Magdalena (Quórum Académico, 2023)
Intercultural communication generates a socially inclusive relationship, with the capacity for dialogue in diversity to balance the hegemonic production of content. The right to communication promotes the possibility of cultural exchange and participation, also contributes to communication for social change. This study measures and characterizes the production of intercultural content in the newspapers La Hora Esmeraldas and El Norte de Imbabura as a policy to democratize communication content. The methodological triangulation between quantitative (content analysis) and qualitative (interviews with journalists) elements respond to approaches and describe the application of the regulations in 2015. In both media, this production has different forms and practices, depending on contexts and actors.